The order and transshipment decisions in a two-location inventory system with demand forecast updates. (September 2019) - Feng, Pingping; Wu, Feng; Fung, Richard Y.K.; Jia, Tao; Zong, Wei
Highlights: The inventory and transshipment problem is studied with demand forecast updates in a two-location inventory system. A two-stage model is developed and backward induction is applied to address the problem. A threshold transshipment policy is proposed. The existence of unique Nash equilibrium is proven. Extensive numerical experiments are conducted to present some valuable findings. Abstract: To improve profitability and reduce demand uncertainty, lateral transshipment is employed in this study to reallocate inventory with updated demand information. A decentralized inventory system with two retailers ordering from one common supplier is analyzed. Each retailer places the order independently before the selling season begins based on original demand forecast. As lead time elapses, more information is collected to update the demand forecast and transshipment is examined. This study constructs a two-stage model and applies backward induction to solve the problem. A threshold transshipment policy is proposed at stage 2. The existence of unique Nash equilibrium is proven at stage 1. Both the centralized system with transshipment and the newsvendor-like system without transshipment are studied as benchmarks to evaluate the performance of transshipment in the decentralized system. Extensive numerical examples are conducted to provide some valuable management implications. The results show that transshipment can lead to profit increase, especially in the system with high informative value of demand forecast updates.